2011
DOI: 10.1371/journal.pone.0027391
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Detectable XMRV and Other MLV-Related Viruses in Healthy Blood Donors in the United States

Abstract: BackgroundPreliminary studies in chronic fatigue syndrome (CFS) patients and XMRV infected animals demonstrated plasma viremia and infection of blood cells with XMRV, indicating the potential risk for transfusion transmission. XMRV and MLV-related virus gene sequences have also been detected in 4–6% of healthy individuals including blood donors in the U.S. These results imply that millions of persons in the U.S. may be carrying the nucleic acid sequences of XMRV and/or MLV-related viruses, which is a serious p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Many studies have failed to detect XMRV in CFS cohorts around the globe. 27 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Surveys also have not identified XMRV infection in the general human population 53 , 54 , 55 , 56 or in humans at high risk for viral infections (e.g., HIV-1-infected individuals). 57 , 58 , 59 , 60 , 61 , 62 …”
Section: Discovery Of Xmrvmentioning
confidence: 99%
“…Many studies have failed to detect XMRV in CFS cohorts around the globe. 27 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 Surveys also have not identified XMRV infection in the general human population 53 , 54 , 55 , 56 or in humans at high risk for viral infections (e.g., HIV-1-infected individuals). 57 , 58 , 59 , 60 , 61 , 62 …”
Section: Discovery Of Xmrvmentioning
confidence: 99%
“…False positives in experimental and clinical diagnoses can be very problematic and, once entered into the scientific literature, can have a lasting, and undeserved, impact. Within the transfusion medicine literature (the area of use for PEGylated RBC), this is readily illustrated by the xenotropic murine leukemia virus-related virus (XMRV) [54,55]. This retrovirus, first described in 2006, was reported to induce both prostate cancer and chronic fatigue-like syndrome [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…These studies, coupled with reported findings in blood plasma, resulted in a perceived risk for transfusable blood products and debate as to whether XMRV testing should be added to the nucleic acid testing (NAT) done on all blood donors in North America and Western Europe. However, carefully controlled studies conducted after the initial XMRV findings suggested that the association of XMRV with human tissue, much less diseased tissues, was an artifact [54,55,58]. Do anti-PEG antibodies exist?…”
Section: Discussionmentioning
confidence: 99%
“…Within blood transfusion, extensive donor studies have been documented. In the United States, 14 834 donors and 2415 linked recipients (Dodd et al , ),110 plasma and 71 PBMC samples from blood donors (NIH blood bank) (Tang et al , ) and in the UK, 23 040 donations (Robinson et al , ).These clearly show an absence of infection and an absence of risk by XMRV to blood safety. However at this time, initial polices of blood services around the world (Table ) have not been reviewed and still reflect the duty of care in response to a disease of unknown aetiology such as CFS/ME.…”
Section: Implications For Tissue Services and Blood Safetymentioning
confidence: 99%